2015
DOI: 10.1104/pp.114.253328
|View full text |Cite
|
Sign up to set email alerts
|

Does Morphological and Anatomical Plasticity during the Vegetative Stage Make Wheat More Tolerant of Water Deficit Stress Than Rice?  

Abstract: District of Columbia 20005 (P.S.B.)Water scarcity and the increasing severity of water deficit stress are major challenges to sustaining irrigated rice (Oryza sativa) production. Despite the technologies developed to reduce the water requirement, rice growth is seriously constrained under water deficit stress compared with other dryland cereals such as wheat (Triticum aestivum). We exposed rice cultivars with contrasting responses to water deficit stress and wheat cultivars well adapted to water-limited condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(107 citation statements)
references
References 66 publications
(63 reference statements)
9
89
0
Order By: Relevance
“…The rice root anatomy is adapted to semiaquatic conditions with characteristic outer sclerenchymatous layer, large cortex diameter, small stele, and xylem (Coudert et al, 2010;Kadam et al, 2015). However, to what extent natural and human selection has shaped root anatomical plasticity in response to water-deficit stress remains to be elucidated.…”
Section: High Degree Of Trait Variability In Response To Waterdeficitmentioning
confidence: 99%
See 2 more Smart Citations
“…The rice root anatomy is adapted to semiaquatic conditions with characteristic outer sclerenchymatous layer, large cortex diameter, small stele, and xylem (Coudert et al, 2010;Kadam et al, 2015). However, to what extent natural and human selection has shaped root anatomical plasticity in response to water-deficit stress remains to be elucidated.…”
Section: High Degree Of Trait Variability In Response To Waterdeficitmentioning
confidence: 99%
“…For instance, the plasticity of root length density in water-deficit stress contributes to rice grain yield stability (Sandhu et al, 2016). Similarly, the comparative analysis between water-deficit tolerant rice and wheat (Triticum aestivum) has demonstrated the functional relevance of plasticity in shoot and root traits to better adapt to water-deficit stress (Kadam et al, 2015). However, phenotypic traits that express constitutively with no plasticity also could provide stress adaptation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Under different types of drought stress, plasticity in root length density or total root length (Kano-Nakata et al, 2011;Tran et al, 2015) and lateral root length and/or branching (Suralta et al, 2010;Kano-Nakata et al, 2013) has been observed to improve shoot biomass, water uptake, and photosynthesis under drought in rice. Plasticity in the level of root aerenchyma development (measured as root porosity) was reported to result in higher shoot dry matter (Niones et al, 2013) and grain yield (Niones et al, 2012) under transient drought stress in rice, and plasticity in other anatomical traits has been hypothesized as a major reason for wheat (Triticum aestivum) being more drought tolerant than rice (Kadam et al, 2015). In a set of 42 native and crop species, plasticity in root depth was a better predictor of shoot response to drought than absolute root depth (Reader et al, 1993).…”
mentioning
confidence: 99%
“…16 A considerable number of such component traits are responsible for the quantitative regulation of utilization of water, the most critical resource under moisture deficit stress conditions, which could vary across diverse plant species and types. [17][18] Tissue water status determines the overall metabolic activity of the cells constituting it, which ultimately underlies the efficacy of various CT mechanisms. Cellular tolerance mechanisms equip each cell to build up a force against drought.…”
Section: How To Unravel the Complexity Of Drought Stressmentioning
confidence: 99%